2011
DOI: 10.1021/ja111104p
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Chelation with Hydroxamate in Histone Deacetylases Modulated by Water Access to the Linker Binding Channel

Abstract: It is of significant biological interest and medical importance to develop class- and isoform-selective histone deacetylases (HDAC) modulators. The impact of the linker component on HDAC inhibition specificity was revealed, but has not been understood. Herein with Born-Oppenheimer ab initio QM/MM molecular dynamics simulations, a state-of-the-art approach to simulating metallo-enzymes, we have found that the hydroxamic acid remains to be protonated upon its binding to HDAC8, and thus disapproved the mechanisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 39 publications
10
97
0
Order By: Relevance
“…As shown in Figure 3 left, optimization of model 1 leads to a structure very similar to the one obtained by Zhang and co-workers 31 where the hydroxamic acid remains uncharged. However, optimization of model 2 leads to a spontaneous proton transfer from SAHA to the nearby histidine H142 with very little reorganization of the remaining QM region.…”
Section: Resultssupporting
confidence: 68%
“…As shown in Figure 3 left, optimization of model 1 leads to a structure very similar to the one obtained by Zhang and co-workers 31 where the hydroxamic acid remains uncharged. However, optimization of model 2 leads to a spontaneous proton transfer from SAHA to the nearby histidine H142 with very little reorganization of the remaining QM region.…”
Section: Resultssupporting
confidence: 68%
“…The HDAC8 H143A mutant has an almost complete loss of activity in contrast to the residual activity of an H142A mutant, in concordance with the proposed model of action (Gantt et al 2010). Furthermore, quantum mechanical/molecular mechanical molecular dynamics simulations suggest that a neutral H143 first serves as the general base to accept a proton from the zincbound water molecule in the initial rate-determining nucleophilic attack step, and then shuttles it to the amide nitrogen atom to facilitate the cleavage of the amide bond (Wu et al 2011). This model seems to be a more likely catalytic mechanism for HDAC-related enzymes, which is similar to the conventional metalloenzymes thermolysin and carboxypeptidase A.…”
Section: Catalytic Mechanisms and Structuressupporting
confidence: 74%
“…The active site comprises a narrow pocket located deep within the protein and contains the zinc metal cofactor. The metal was pentacoordinated by His183, Asp181, and Asp269 [32]. Docking results also showed a bidentate coordination through the carbonyl and hydroxyl groups of the ligand hydroxamate moieties (Fig.…”
Section: Docking Resultsmentioning
confidence: 88%
“…The 3D structures of the compounds were created and subsequently subjected to energy minimized to within an rms gradient of 0.1 kcal/mol/Å using MOE 2009.10 package, setting the force field to the 94s variant of the Merck molecular force field 94s [31]. Various studies have suggested negative hydroxamate-Zn 2+ coordination in the active site of HDACs [32] and linked with several experimental results. Therefore, the HA inhibitors were deprotonated after importing the 3D structures to MOE database.…”
Section: Preparation Of the Ligandsmentioning
confidence: 99%